The 10th anniversary of the Paris agreement on climate: unmet goals and unanswered questions - Vineis, Paolo; Orsini, Raimondo; Vacchiano, Giorgio (Frontiers in Public Health, 2025)
The contribution of interventions for mitigation of climate change in different sectors has been evaluated by IPCC in their 6th report (AR6) and by the International Energy Agency (IEA), among others. However, these scientific evaluations have not been translated into a systematic, overall appraisal, that combines the few quantified targets, such as greenhouse gas emissions and temperature trajectories, with broader but less quantified dimensions such as feasibility, equity, justice, co-benefits (including health), and acceptability. These aspects remain fragmented or insufficiently assessed at the global scale, as a large number of questions are still open on the suitability of different mitigation measures. Progress has been made in certain sectors, such as the phase-out of coal in many countries; the first substantial consideration of health at COP27 and the growing attention to its impacts; the renewed focus on Net Zero commitments; the launch of the European Union's “Fit for 55” package, toward which the EU is nearly on track as of 2025; and the recognition of the need to connect climate action with local benefits, including for health. But such progress is still insufficient. The purpose of this perspective is to identify gaps in a coordinated international action, and in particular the open questions concerning priorities and feasibility of different mitigation strategies, with special emphasis on health.